The Effect Of Education On Income Inequality In Selected Islamic Countries - Shahabadi, Abolfazl; Nemati, Morteza; Hosseinidoust, Seyed Ehsan (Penerbit Universiti Sains Malaysia (USM Press), 2018)
The impact of education on income inequality remains a challenging issue at the core of economic debates. The present study attempts to investigate the eﬀect of income inequality in a selection of Islamic countries during 1990–2013. Method of panel data has been implemented, and the fxed eﬀects are examined against the random ones by the Hausman test. The impacts of gross domestic product (GDP) and training at primary, secondary and university levels on income inequality is investigated in the selected Islamic countries. Findings indicate that the enrolment rate in primary and secondary schools has a signifcant negative eﬀect on income inequality, and the enrolment rate in university has a signifcant positive eﬀect on income inequality. Thus, training in primary and secondary schools might reduce income inequality, and education in universities can increase income inequality because of the higher fnancial capability of certain classes of people and the expertise they have acquired.